Reduced fetal growth velocities and the association with neonatal outcomes in appropriate-for-gestational-age neonates: a retrospective cohort study - M. L. E. Hendrix; S. M. J. van Kuijk; A. W. D. Gavilanes; D. Kramer; M. E. A. Spaanderman; S. Al Nasiry (BMC, 2019)
Abstract Background Fetal growth restriction is, despite advances in neonatal care and uptake of antenatal ultrasound scanning, still a major cause of perinatal morbidity. Neonates with birth weight > 10th percentile are assumed to be appropriate-for-gestational-age (AGA), although many are at increased risk of perinatal morbidity, because of undetected mild restriction of growth potential. We hypothesized that within AGA neonates, reduced fetal growth velocities are associated with adverse neonatal outcome. Methods A retrospective cohort study of singleton pregnancies, in the Maastricht University Medical Centre (MUMC) between 2010 and 2016. Women had two fetal biometry scans (18-22 weeks and 30-34 weeks of gestational age) and delivered a newborn with a birth weight between the 10th-80th percentile. Differences in growth velocities of the abdominal circumference (AC), biparietal diameter (BPD), head circumference (HC) and femur length (FL) were compared between the suboptimal AGA (sAGA) (birth weight centiles 10-50) and optimal AGA (oAGA) (birth weight centiles 50-80) group. We assessed the association between velocities and neonatal outcomes. Results We included 934 singleton pregnancies. In the suboptimal AGA group, fetal growth velocities were lower (in mm/week): AC 10.72 ± 1.00 vs 11.23 ± 1.00 (p < .001), HC 10.50 ± 0.80 vs 10.68 ± 0.77 (p = 0.001), BPD 3.01 ± 0.28 vs 3.08 ± 0.27 (p < .0001) and FL 2.47 ± 0.21 vs 2.50 ± 0.22 (p = 0.014), compared to the optimal AGA group. Neonates with an adverse neonatal outcome had significantly lower growth velocities (in mm/week) of: AC 10.57 vs 10.94 (p = 0.034), HC 10.28 vs 10.59 (p = 0.003) and BPD 2.97 vs 3.04 (p = 0.043) compared to those with normal outcome. An inverse association was observed between the AC velocity and a composite adverse neonatal outcome (OR) = 0.667 (95%CI 0.507-0.879, p = 0.004), and between the AC velocity and neonates with NICU stay (OR) = 0.733 (95%CI 0.570-0.942, p = 0.015). Neonates with a birthweight lower than expected (based on the abdominal circumference at 20 weeks) had significantly more composite adverse neonatal outcomes 8.5% vs 5.0% (p = 0.047), NICU stays 9.6% vs 3.8% (p < .0001) and hospital stays 44.4% vs 35.6% (p = 0.006). Conclusions Appropriate-for-gestational-age neonates are a heterogeneous group with some showing suboptimal fetal growth. Abnormal fetal growth velocities, especially abdominal circumference velocity, are associated with adverse neonatal outcome and can potentially improve the detection of mild growth restriction when used in multivariate models.